Physiological and molecular analysis of the interaction between aluminium toxicity and drought stress in common bean (Phaseolus vulgaris) - Yang, Z.B.; Eticha, D; Albacete, A; Rao, Idupulapati M.; Roitsch, T; Horst, Walter J. (Oxford University Press, 2012)
Aluminium (Al) toxicity and drought are two major factors limiting common bean (Phaseolus vulgaris) production in the tropics. Short-term effects of Al toxicity and drought stress on root growth in acid, Al-toxic soil were studied, with special emphasis on Al–drought interaction in the root apex. Root elongation was inhibited by both Al and drought. Combined stresses resulted in a more severe inhibition of root elongation than either stress alone. This result was different from the alleviation of Al toxicity by osmotic stress (–0.60 MPa polyethylene glycol) in hydroponics. However, drought reduced the impact of Al on the root tip, as indicated by the reduction of Al-induced callose formation and MATE expression. Combined Al and drought stress enhanced up-regulation of ACCO expression and synthesis of zeatin riboside, reduced drought-enhanced abscisic acid (ABA) concentration, and expression of NCED involved in ABA biosynthesis and the transcription factors bZIP and MYB, thus affecting the regulation of ABA-dependent genes (SUS, PvLEA18, KS-DHN, and LTP) in root tips. The results provide circumstantial evidence that in soil, drought alleviates Al injury, but Al renders the root apex more drought-sensitive, particularly by impacting the gene regulatory network involved in ABA signal transduction and cross-talk with other phytohormones necessary for maintaining root growth under drought.